2011
DOI: 10.1111/j.1365-2672.2011.04977.x
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of bacterial vaginosis

Abstract: Summary Bacterial vaginosis (BV) is the most common vaginal infection among women of childbearing age. This condition is notorious for causing severe complications related to the reproductive health of women. Five decades of intense research established many risk factors for acquisition of BV; however, because of the complexity of BV and lack of a reliable animal model for this condition, its exact aetiology remains elusive. In this manuscript, we use a historical perspective to critically review the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
170
1
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 198 publications
(326 reference statements)
1
170
1
16
Order By: Relevance
“…Qualitative studies using conventional culture methods have characterized over 100 separate phenotypes that can be isolated from the vaginal microbiome, with some phenotypes always being present in high numbers when assessed longitudinally and some phenotypes being present only sporadically, while other phenotypes are consistently present in low numbers (3)(4)(5). It has been shown that certain species of Lactobacillus (Lactobacillus crispatus, L. jensenii, L. gasseri, and L. iners) are more common than others in overtly healthy women, while species of obligately anaerobic rods of the genera Atopobium, Prevotella, Mobiluncus, and Sneathia are more commonly present in women with symptoms of bacterial vaginosis (7)(8)(9)(10)(11)(12)(13). More recent studies using both molecular and advanced culture methods (see below) suggest that what can be considered normal or abnormal occurs on a complex biological spectrum that indicates a greater microbiological diversity for BV than previously thought.…”
mentioning
confidence: 99%
“…Qualitative studies using conventional culture methods have characterized over 100 separate phenotypes that can be isolated from the vaginal microbiome, with some phenotypes always being present in high numbers when assessed longitudinally and some phenotypes being present only sporadically, while other phenotypes are consistently present in low numbers (3)(4)(5). It has been shown that certain species of Lactobacillus (Lactobacillus crispatus, L. jensenii, L. gasseri, and L. iners) are more common than others in overtly healthy women, while species of obligately anaerobic rods of the genera Atopobium, Prevotella, Mobiluncus, and Sneathia are more commonly present in women with symptoms of bacterial vaginosis (7)(8)(9)(10)(11)(12)(13). More recent studies using both molecular and advanced culture methods (see below) suggest that what can be considered normal or abnormal occurs on a complex biological spectrum that indicates a greater microbiological diversity for BV than previously thought.…”
mentioning
confidence: 99%
“…Theoretically, the inception of pregnancy complications as a result of BV is due to its potential to favor ascending infections (from the vagina to the chorioamnion) to cause inflammation of the choriodecidual space and activating pathways of labor and subsequently PTD and PTB (Guerra et al, 2006;Denney and Culhane, 2009;Guédou et al, 2013). BV-related bacteria and the toxins produced by these bacteria can cross the placenta and result in fetal complications (Turovskiy et al, 2011).…”
Section: Complications Associated With Bacterial Vaginosismentioning
confidence: 99%
“…The concept of male-to-female heterosexual transmission is opposed by (i) the treatment of male partners that is not beneficial as it does not result in a decline in BV prevalence and (ii) the fact that there is no solitary etiological agent responsible for BV (Turovskiy et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also compete with potentially pathogenic bacteria for space and nutrients [4,6,7]. Moreover, healthy vaginal microbiota may also be composed by pathogenic bacteria, such as Gardnerella vaginalis, in low numbers, coexisting in equilibrium with Lactobacillus species [8].…”
Section: Introductionmentioning
confidence: 99%